A Case of Infective Endocarditis and Pulmonary Septic Emboli Caused by Lactococcus lactis - Bshara Mansour; Adib Habib; Nazih Asli; Yuval Geffen; Dan Miron; Nael Elias (Hindawi Limited, 2016)
Infective endocarditis is a rare condition in children with normal hearts. We present here a case of previously healthy eleven-year-old girl with infective endocarditis and pulmonary septic emboli caused by a very rare bacterial etiology (Lactococcus lactis). Identification of this pathogen was only made by polymerase chain reaction.